Identifying the opportunities and barriers: a cross-sectional review of the health development coordination mechanisms in the World Health Organization African Region - Usman, Abdulmumini; Olu, Olushayo Oluseun; Kakay, Mohamed; Ba, Ndoungou Salla; Kabore, Patrick; Kulausa, Hyelni; Chanda, Emmanuel; Gasasira, Alex; Cabore, Joseph (Frontiers in Public Health, 2025)
Effective health sector coordination is essential to improve the implementation of development and humanitarian response programmes in the WHO African Region. In recent years, multiple efforts have been deployed to strengthen coordination mechanisms, with uneven progress depending on the national context. Nevertheless, important challenges remain. In many cases, mechanisms remain fragmented, coordination platforms often operate in isolation, and resources are not always used efficiently. In certain settings, current cooperation models may hinder the long-term sustainability of progress, and there is a need to foster greater synergy among the actors involved. Strengthening national capacities and promoting coordination that better responds to realities on the ground therefore remain critical priorities on the continent. While several studies have assessed coordination mechanisms in individual countries, a regional overview has been lacking. This study thus aimed to examine the current status and characteristics of health sector coordination mechanisms and the role of WHO in health coordination across the 47 member states of the WHO African Region. A descriptive cross-sectional study was conducted between 2017 and 2019 using a mixed-methods approach, including document reviews, key informant interviews, and focus group discussions. The findings revealed that only 9 member states (23%) had a functioning central health sector coordination platform, all of which had signed the IHP + compact and adopted the Sector-Wide Approach. Nearly half (47%) lacked a central platform, despite 41% hosting a significant number of development partners and 36% having signed the IHP+. Sixteen member states (34%) operated multiple fragmented, programme-specific coordination mechanisms with minimal linkage to any overarching platform, despite most of them (81%) being IHP + signatories. In eight member states, parallel humanitarian and development coordination systems coexisted. Coordination was identified by stakeholders as one of the top five priorities for WHO support. Based on these findings, five key recommendations are proposed: strengthening national coordination capacities; streamlining multiple coordination mechanisms; addressing coordination challenges in protracted crisis settings; clearly defining WHO’s coordination role in line with partner expectations; and providing context-specific support across core health system functions. Collective efforts from all stakeholders are essential to accelerate the implementation of these recommendations, thereby enhancing health governance, improving aid effectiveness, and advancing progress towarduniversal health coverage in the region.